The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1159/000182506
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Hyperparathyroidism in Severe Uremics Following Very Low-Protein and Low-Phosphorus Diet

Abstract: Serum iPTH levels decreased markedly in 16 severe chronic uremic patients who changed from a standard low-protein diet to a very low-nitrogen and very low-phosphorus diet supplemented with essential amino acids and keto-analogues and with calcium. The fall of serum iPTH levels occurred simultaneously with a fall of serum phosphate and an increase of serum calcium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 13 publications
1
17
0
1
Order By: Relevance
“…These results confirm our previous observations of a similar effect exerted by dietary treatment on circulating NH 2 - and C-terminal PTH fragments [4]. More recently, Lafage et al [6] and Combe and Aparicio [7] demonstrated the reversal of secondary hyperparathyroidism and some favorable effects on bone metabolism exerted by a similar dietary regimen associated with native vitamin D administration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results confirm our previous observations of a similar effect exerted by dietary treatment on circulating NH 2 - and C-terminal PTH fragments [4]. More recently, Lafage et al [6] and Combe and Aparicio [7] demonstrated the reversal of secondary hyperparathyroidism and some favorable effects on bone metabolism exerted by a similar dietary regimen associated with native vitamin D administration.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, correction of hyperphosphatemia and hypocalcemia by lowering dietary phosphorus intake and by the administration of calcium-containing phosphate binders is the first target of therapeutic intervention [4], whereas the use of vitamin D derivatives is questionable, in predialysis patients at least [5]. …”
Section: Introductionmentioning
confidence: 99%
“…LPD was low in cysteine and methionine, and therefore had a low acid content. Barsotti et al [30,31] have shown that correcting metabolic acidosis induces reduction in plasma phosphate level without any change in the body pool of phosphate. This probably results from the translocation of phosphate from an extracellular to an intracellular site.…”
Section: Discussionmentioning
confidence: 99%
“…These patients had been undergoing conservative therapy from ten to 22 months when the initial study was carried out. They were following a nitrogen-restricted diet containing high quality, low phosphorus proteins or keto-analogs of essential amino acids (Giovannetti and Maggiore, 1964;Barsotti et al, 1982). During this treatment, their serum creatinine ranged from 4 to 8 mg/lOO ml.…”
Section: Methodsmentioning
confidence: 99%